Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Kerja Auditor Internal Pada PT. Herfinta Farm & Plantation - Fany Renaldy Harahap; Nurhayati Nurhayati (STIKes Ibnu Sina Ajibarang, 2023)
PT.Herfinta Farm & Plantion is one of the industries related to plantations and business (agriculture). This study aims to determine the factors that influence the quality of work of Internal Auditors at PT. Herfinta Farm & Plantation. This research is included in the category of observational research using qualitative methods, based on subjects and results. The value of one or more variables is determined through a descriptive study, which does not require similarities or associations between one variable and another. In qualitative research, the focus is more on quality than quantity, and the data collected is done through interviews, direct observation, and other relevant official documents rather than surveys conducted. The population of this study consisted of three people, namely the head of section (Kabag), Internal Audit Agronomy, and staff working in the Audit Department at PT. Herfinta Farm & Plantation. From the research conducted, that the factors that influence the quality of work of the Internal Auditor at PT. Herfinta Fam & Plantation is audit knowledge, accountability and motivation.